LabVIEW Based Fuzzy Controller Designed for a Microwave Oven - Sura Nawfal Abd Alrazaaq (Tikrit Journal of Engineering Sciences, 2016)
This paper presents a new design for controlling microwave oven (MWO) device which has become used daily in last few years. The aim of this work is to develop the operation of the recent MWOs, where three new features have been proposed to be supplemented to the new design, the first one is adding a load cell under a turntable specified for MWO to measure the weight of the processed food instead of setting it manually. The second feature is incorporating the fuzzy techniques with the design of MWO by designing a fuzzy controller capable to decide the suitable power level and total heating time automatically according to the measured weight. While in the third feature a steam sensor has been suggested to be added in the upper cavity of the MWO, so the controller will be able to decide the remaining time to finish once the presence of a steam is detected. Finally the output results of the controller have been tested practically on some kinds of food using the available MWO. The results proved the efficiency of using this design by finding the suitable parameters to process food without dependence on the repeated estimation by the user.